A novel ultrasound technique based on piezoelectric diaphragms applied to material removal monitoring in the grinding process - Alexandre, Felipe A. [UNESP]; Aguiar, Paulo R. [UNESP]; Götz, Reinaldo [UNESP]; Viera, Martin Antonio Aulestia [UNESP]; Lopes, Thiago Glissoi [UNESP]; Bianchi, Eduardo Carlos [UNESP] (MDPI, 2019)
The interest of the scientific community for ultrasound techniques has increased in recent years due to its wide range of applications. A continuous effort of researchers and industries has been made in order to improve and increase the applicability of non-destructive evaluations (NDE). In this context, the monitoring of manufacturing processes, such as the grinding process, arises. This work proposes a novel technique of ultrasound monitoring (chirp-through-transmission) through low-cost piezoelectric diaphragms and digital signal processing. The proposed technique was applied to the monitoring of material removal during the grinding process. The technique is based on changes in ultrasonic waves when propagated through the material under study, with the difference that this technique does not use traditional parameters of ultrasonic techniques but digital signal processing (RMS and Counts). Furthermore, the novelty of the proposed technique is also the use of low-cost piezoelectric diaphragms in the emission and reception of ultrasonic waves, enabling the implementation of a low-cost monitoring system. The results show that the monitoring technique proposed in this work, when used in conjunction with the frequency band selection, is sensitive to the material removal in the grinding process and therefore presents an advance for monitoring the grinding processes.
Keywords: Digital signal processing; Grinding monitoring; Piezoelectric transducers; Ultrasound technique